2002
DOI: 10.1557/proc-713-jj1.7
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis for Long-Term Degradation of Waste Package at the Potential Yucca Mountain Repository for High-Level Nuclear Waste Disposal

Abstract: The technical basis for Site Recommendation (SR) of the potential repository for high-level nuclear waste at Yucca Mountain, Nevada has been completed. Long-term containment of the waste and subsequent slow release of radionuclides from the engineered barrier system (EBS) into the geosphere will rely on a robust waste package (WP) design, among other EBS components as well as the natural barrier system. The WP and drip shield (DS) degradation analyses for the total system performance assessment (TSPA) baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Although it is commonly assumed that the container no longer serves any function after first penetration of the corrosion allowance, some PA models do account for the effect of the remaining barrier. For example, in the Waste Package Degradation (WAPDEG) PA model for the corrosion of Alloy 22 waste packages in the Yucca Mountain repository, the container surface was divided into ~1400 "patches", each approximately the size of a corrosion coupon used in the complementary long-term corrosion tests used to provide input data for the model [25][26][27]. Each patch was assigned a corrosion rate from a Weibull distribution of the experimentally observed rates, so that some patches corroded faster than others.…”
Section: Pa Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although it is commonly assumed that the container no longer serves any function after first penetration of the corrosion allowance, some PA models do account for the effect of the remaining barrier. For example, in the Waste Package Degradation (WAPDEG) PA model for the corrosion of Alloy 22 waste packages in the Yucca Mountain repository, the container surface was divided into ~1400 "patches", each approximately the size of a corrosion coupon used in the complementary long-term corrosion tests used to provide input data for the model [25][26][27]. Each patch was assigned a corrosion rate from a Weibull distribution of the experimentally observed rates, so that some patches corroded faster than others.…”
Section: Pa Modelsmentioning
confidence: 99%
“…Therefore, for models that included a DS, failure of the DS was a prerequisite factor for localized corrosion. In the CNWRA [81] and DOE [12,82,83] models, the initiation of crevice corrosion was assessed based on the electrochemical criterion E CORR ≥ E RCREV , where E RCREV is the crevice repassivation potential (also see the discussion in Section 3.2.4 of [1]). DOE screened out localized corrosion based on these various criteria for the initiation of crevice corrosion and concluded that localized attack was not possible at any time in the evolution of the repository environment (Figure 5).…”
Section: Hic Of Ds Based On Rate Of H Absorption and Threshold [H Abs...mentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate the long-term safety of Yucca Mountain, Wilson et al (2002) conducted the total-system performance-assessment simulations and found that risk was dominated by igneous activity at early times, because the robust waste-package design prevented significant nominal (nondisruptive) releases for tens of thousands of years. The technical basis for Site Recommendation (SR) of the potential repository for high-level nuclear waste at Yucca Mountain was reviewed (Lee et al, 2002a), showing that longterm containment of the waste and subsequent slow release of radionuclides from the engineered barrier system (EBS) into the geosphere relied on a robust waste package (WP) design, among other EBS components as well as the natural barrier system. The WP and drip shield (DS) degradation analyses for the total system performance assessment (TSPA) baseline model for the SR showed that, based on the current corrosion models and assumptions, both the DSs and WPs did not fall within the regulatory compliance time period (10,000 yr).…”
mentioning
confidence: 99%